Implementasi Peraturan Badan Pengatur Hilir Minyak Dan Gas Bumi Nomor 06 Tahun 2015 tentang Penyaluran Jenis Bahan Bakar Minyak Tertentu dan Jenis Bahan Bakar Khusus Penugasan pada Daerah Tanpa Penyalur di Kabupaten Katingan - Laksminarti Laksminarti; Nova Riyanti (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2018)
This study aims to determine the implementation of the Regulation of the Downstream Oil and Gas Regulatory Agency Number 06 of 2015 concerning Distribution of Specific Types of Oil Fuels and Types of Fuels Specifically for Assignments to Areas without Distributors in Katingan District. The type of research used is qualitative research methods with descriptive analysis techniques. Data collection techniques used were observation, interviews, and documentation. The informants taken in this study were carried out using the snowball sampling technique. Based on the results of the research based on the results of research on the implementation of the Regulation of the Downstream Oil and Gas Regulatory Agency Number 06 of 2015 it can be concluded that the regulation cannot be implemented. This is indicated by the absence of the establishment of sub-distributors and the appointment of sub-distributors. Suggestions that researchers can give to the local government of Katingan Regency should consider the needs of regions with limited distribution so that researchers feel the need to establish sub-distributors that can empower community groups through cooperatives and Village-Owned Enterprises.